Penerapan Data Mining Klasifikasi Lahan Tanam Buah Alpukat dengan Algoritma Naïve Bayes - Fidiyanto, Nur; Izzati, Afifah Nurul (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2024)
The avocado plant is a plant that came into Indonesia in the 18th century. It originated in Central America under the Latin name Persea Americana Mill. Avocado plants have many different varieties and the majority grow fertile in the tropics. Nevertheless, there are differences in growing needs between different types of avocado crops when planted on different crops. As in this study where in the observation of the research on the growth differences between avocado plants of type miki and shepard on the grown land of KTH Pedunung Lestari Welfare Village Purworejo Prefecture Pungging district of Mojokerto. In this case, it is necessary to determine exactly what type of avocado plants are suitable to be planted on the land of KTH Pedunung Lestari Sejahtera. The research was conducted using the Naïve Bayes algorithm method. Based on observations, interviews with sources and library studies, the most influential variables are ground height (Mdpl), Temperature (°C), Rainfall (mm/day) and Soil type. In this study, the results were obtained on the land of KTH Pedunung Lestari Sejahtera with a land height of 250 Mdpl, temperature 18°C, rainfall 25 mm/day and humus soil type, more suitable for planting avocado type miki than shepard type. Based on the calculations on miki avocado, the value of "Yes" is 0.75 and "No" is 0,25, while shepard type has a value of “Yes” of 0 and “No” of 1. The value of accuracy is 50%, Precision is 43% and Recall is 100%.